Bunyi Forman Vokal dalam Bahasa Jawa Ngoko: Kajian Fonetik Akustik - Mentari, Suci; Ganie, Rohani; Syarfina, Tengku (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The Javanese language (BJ) is divided into three, namely Ngoko, Krama Madya, and Krama Inggil. BJ consists of 10 vowel sounds: [i, I, e, ɛ, a, ǝ, o, ɔ, U, u]. This study aims to determine the values of BJ vowel sounds based on FORMAN data analysis, comparing the voices of male speakers (PL) and female speakers (PP). Additionally, the study aims to identify the more dominant vowel sounds based on gender. The qualitative method was used to collect data on the vowel sounds of Ngoko Javanese (BJN) by analyzing voice recordings using the Praat application program. The quantitative method was employed to calculate the FORMAN F1, F2, and F3 values and determine the average difference in BJN vowel sounds. Data from the BJ dictionary, consisting of 10 words with vowel sounds at the beginning, were used for analysis. The results showed that in PL, the highest vowel values were: [u] at 3089Hz, [i] at 3918Hz, [ɔ] at 3535Hz, and [ɛ] at 3228Hz. The lowest vowel values were: [ɛ] at 277Hz, [U] at 431Hz, and [i] at 336Hz. In PP, the highest vowel values were: [ɛ] at 3021Hz, [i] at 3200Hz, [I] at 3083Hz, and [o] at 3367Hz. The lowest vowel values were: [e] at 391Hz, [I] at 525Hz, [ɛ] at 385Hz, and [i] at 455Hz. In conclusion, BJN consists of 10 vowel sounds, with the highest vowel sound being [ɔ] and the lowest vowel sound being [i] in PL. The comparison of vowel sounds at the beginning of words in PL and PP in BJN, based on the high and low sounds of the F1, F2, and F3 vowel sounds, indicates that PL is more dominant.